A STUDY ON THE RELATIONSHIP BETWEEN CUSTOMER SATISFACTION AND EXPECTATION GAP - Dari, Chimgee; Batgerel, Ulaanbaatar; Oyungerel, Gurragchaa (Journal of Business and Innovation (Бизнес & Инноваци), 2025)
Understanding the relationship between service quality, pricing strategy, and customer satisfaction in Mongolian restaurants is essential for business growth and fostering customer loyalty. This study conducts a comparative statistical analysis of customer evaluations between two restaurants “Modern Nomads” and “Bluefin” using SPSS software. The research aims to highlight significant differences in customer perceptions and to identify factors that influence satisfaction through reliability testing, including сronbach’s аlpha.